Step-by-step explanation:
Inverse of
y
=
x
+
3
x
−
2
is
y
=
2
x
+
3
x
−
1
Explanation:
As
y
=
x
+
3
x
−
2
x
y
−
2
y
=
x
+
3
or
x
y
−
x
=
2
y
+
3
or
x
(
y
−
1
)
=
2
y
+
3
or
x
=
2
y
+
3
y
−
1
Hence inverse of
y
=
x
+
3
x
−
2
is
y
=
2
x
+
3
x
−
1
Observe that each of the function is a reflection of the other in the line
x
=
y
.
graph{(y-(x+3)/(x-2))(y-(2x+3)/(x-1))(x-y)=0 [-10, 10, -5, 5]}
2x^2 - 8x - 24
First, we can factor a 2 out of this expression to simplify it.
2(x^2 - 4x - 12)
Now, we can try factoring this two ways: by using the quadratic formula, or by using the AC method.
We're gonna try using the AC method first.
List factors of -12.
1 * -12
-1 * 12
2 * -6
-2 * 6 (these digits satisfy the criteria.)
Split the middle term.
2(x^2 - 2x + 6x - 12)
Factor by grouping.
2(x(x - 2) + 6(x - 2)
Rearrange terms.
<h3><u>(2)(x + 6)(x - 2) is the fully factored form of the given polynomial.</u></h3>
Answer:
$3,787
Step-by-step explanation:
frist find the amount of intrest
3,500 X 0.082 X 1 = 287
next add the oragial amount to the amount of intrest
3,500 + 287 = 3,787
Answer:
42
Step-by-step explanation:
39+39 = 78
162 - 78 = 2 lengths =84
84/2 = 42
i would pick number C) since i think it would be the correct answer